Accelerating the Achievement of Sustainable Development Goals for the Improvement and Equitable Distribution of Population Heal 2016
DOI: 10.26911/theicph.2016.057
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening and Test of Antioxidant Activity in the Extract of Mangosteen Rind

Abstract: BACKGROUND: Mangosteen (Garcinia mangostana L.) rind had been known as an agriculture waste. However, some recent studies reported that Mangosteen rind had some health benefit. The rind (skin) of Mangosteen fruit was reported to contain compounds such as xanthones and anthocyanin antioxidants. There is a need to examine the chemical compound content of Mangosteen rind and the activities of antioxidants contained in the Mangosteen rind, so as to increase natural source of antioxidants for human health. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Following the methanol extraction method, it was found that MPE includes six secondary metabolites (see Table 2 ). It has been reported that MPE does contain many alkaloids, polyphenols, flavonoids, tannins, saponins, and quinones [ 32 ]. Therefore, MPE is known to have high antioxidant properties [ 3 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Following the methanol extraction method, it was found that MPE includes six secondary metabolites (see Table 2 ). It has been reported that MPE does contain many alkaloids, polyphenols, flavonoids, tannins, saponins, and quinones [ 32 ]. Therefore, MPE is known to have high antioxidant properties [ 3 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Saponins inhibit growth and embryonic development. Saponins can be absorbed, resulting in osmotic power, and the embryo becomes unbalanced, causing embryonic fluid to be absorbed out of the membrane and the embryo cells to shrink as a result of plasmolysis, and ultimately, the embryo will die 13,14 .…”
Section: Hatching Ratementioning
confidence: 99%
“…According to the ethanol extraction method, MPE contains six secondary metabolites (see Table 2). MPE has been found to possess a high concentration of polyphenols, flavonoids, tannins, saponins, and quinones (14). As a result, MPE is recognized to have solid antioxidant capabilities (15,16).…”
Section: Extract Propertiesmentioning
confidence: 99%